The Transformation of Web-Based Learning: A Case Study in Junior and Senior High Schools - Dzakiyah 'Izzah Ghassani Adsumi; Rhaesa Fadillah Rahmadani; Dede Nurazizah; Surya Amami Pramuditya (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Web-based learning has great potential to simplify complex material to be more easily understood. However, the implementation of web-based learning also has a number of challenges, one of which is the limited technological infrastructure and the adaptability of students and teachers to the use of digital media. The purpose of this study is to determine the effectiveness that occurs in the learning process after the implementation of websites such as Google Sites and microsites. This research uses ADDIE research method. However, this study did not reach the implementation stage. The subjects of this study consisted of students with 3 different schools with details, namely 5 10th grade students of MAN 1 Cirebon Regency, 5 10th grade students of SMA 6 Cirebon, and 4 9th grade students of SMP Negeri 16 Cirebon. This research instrument uses open interviews with several students. Based on the results of open interviews with several students with 3 different schools that web-based learning using Google Sites and microsite is considered very interesting and fun by students, because it has an interactive display. The use of Google Sites and microsites in mathematics learning has shown effective results in improving student engagement and the quality of the learning process. Flexible access to materials allows students to learn independently. Students benefit from the easy access to information, performing.